2004
DOI: 10.1007/bf03218421
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of salt concentration on the glass transition temperature and ionic conductivity of poly(ethylene glycol)-polyurethane/LiClO4 complexes

Abstract: Solid polymer electrolytes based on poly(ethylene glycol)-polyurethane (PEG-PU) complexed with LiClO 4 salt have been prepared by the solvent casting method. A PEG-PU material (PEG:4,4'-diphenylmethane diisocyanate:1,4-butanediol = 1:2:1) was synthesized through a typical two-step condensation reaction. We investigated the effects of the salt concentration on the ionic conductivity (σ) and the glass transition temperature (T g ) of the complex electrolytes by using alternating current impedance spectroscopy, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 15 publications
5
10
0
Order By: Relevance
“…A high salt content renders lithium ions available for coordination with PEG units, thereby reducing the tendency to form crystalline phases. In accordance with a general trend, the T g of polymer–salt complexes increases with the addition of salt due to the formation of transient crosslinking between polymer chains via the coordinated interaction between the polymer chains and salt . The same trend was observed in both kinds of crosslinked network polymers in this study owing to the formation of transient crosslinking, as shown in Table .…”
Section: Resultssupporting
confidence: 89%
“…A high salt content renders lithium ions available for coordination with PEG units, thereby reducing the tendency to form crystalline phases. In accordance with a general trend, the T g of polymer–salt complexes increases with the addition of salt due to the formation of transient crosslinking between polymer chains via the coordinated interaction between the polymer chains and salt . The same trend was observed in both kinds of crosslinked network polymers in this study owing to the formation of transient crosslinking, as shown in Table .…”
Section: Resultssupporting
confidence: 89%
“…According to Bhattacharya et al [35] systems containing salt with smaller cations exhibit higher conductivity due to higher mobility of the cation. The conductivity values obtained in this work are comparable with that reported by Huh et al [34], which is 2.6 × 10…”
Section: Room Temperature Conductivitysupporting
confidence: 91%
“…At high salt concentration, the distance between dissociated ions became too close to each other enabling them to recombine into neutral ion-pairs and do not contribute to conductivity. Such phenomenon has also been reported in the literature [17,33,34]. By comparing the systems containing LiI and NaI, the conductivity is higher for PU-LiI compared to that for PU-NaI due to the size of cations.…”
Section: Room Temperature Conductivitysupporting
confidence: 83%
“…In fact, as mentioned before, there is usually a difference of 10–15°C or so between the values of T g determined by the DSC and DMTA techniques. 37…”
Section: Resultsmentioning
confidence: 99%
“…In fact, as mentioned before, there is usually a difference of 10-15 C or so between the values of T g determined by the DSC and DMTA techniques. 37 T g values of PS-filled silica versus filler volume fraction are plotted for both dynamic and thermal mode in Figure 3. The slope of T g curve is a proper parameter for determining T g shift velocity, which is due to nanoparticle size.…”
Section: Thermal Studymentioning
confidence: 99%